Enriching Glucoraphanin in Brassica rapa Through Replacement of BrAOP2.2/BrAOP2.3 with Non-functional Genes - Liu, Zhiyuan; Liang, Jianli; Zheng, Shuning; Zhang, Jifang; Wu, Jian; Cheng, Feng; Yang, Wencai; Wang, Xiaowu (Frontiers in Plant Science, 2017)
Sulforaphane, the hydrolytic product of glucoraphanin glucosinolate, is a potent anticarcinogen that possesses preventive effects against several human cancers. However, in most B. rapa vegetables, glucoraphanin is undetectable or only present in trace amounts, since the glucoraphanin that is present is converted to gluconapin by three functional BrAOP2 genes. In this study, to enrich beneficial glucoraphanin content in B. rapa, the functional BrAOP2 alleles were replaced by non-functional counterparts through marker-assisted backcrossing. We identified non-functional mutations of two BrAOP2 genes from B. rapa. The backcross progenies with introgression of both non-functional braop2.2 and braop2.3 alleles significantly increased the glucoraphanin content by 18 times relative to the recurrent parent. In contrast, replacement or introgression of single non-functional braop2.2 or braop2.3 locus did not change glucoraphanin content. Our results suggest that replacement of these two functional BrAOP2 genes with non-functional alleles has the potential for producing improved Brassica crops with enriched beneficial glucoraphanin content.